German FLAK in WWII, 1939-1945 - Müller, Werner (Schiffer military/aviation history, 1998)
This volume is a valuable illustrated documentation of German Flak guns, using photos largely unpublished to date, and includes their use on all fronts in both the air and ground roles. Included are the 37mm, 105mm and 128mm guns and especially the famed 88mm.